(untitled) (Research, Society and Development, 2022)
Biomaterials are intended to replace or repair tissues through interaction with biological systems. Being materials of synthetic or natural origin. This article aims to describe the use of biomaterials in dentistry. The literature searches took place on the following platforms: Scientifc Eletrônica Online Library (SCIELO), Google Scholar and Medical Literature Analysis and Retrieval System Online (PubMed), selected according to the proposed theme. Polymer, ceramics, and metal are the raw materials used in the manufacture of biomaterials, which require biological, physical and mechanical properties, because there is an interaction that can interfere with the homeostasis of the individual. Cell proliferation, elasticity, color, corrosion resistance, biocompatibility, rupture resistance and permeability are observed. The clinical application of molding material, composite resin, suture threads, previous crowns, facets, implants, grafts, among others is described here. With the studies it is understood that the scaffolds provide improvement in the regeneration of bone tissue.